Amphiphilic Glycoconjugated Porphyrin Heterodimers as Two‐Photon Excitable Photosensitizers: Design, Synthesis, Photophysical and Photobiological Studies. Issue 6 (13th February 2018) - Chen, Su; Poyer, Florent; Garcia, Guillaume; Fiorini‐Debuisschert, Céline; Rosilio, Véronique; Maillard, Philippe
Abstract: A new family of amphiphilic glycoconjugated porphyrin dimers usable in two‐photon photodynamic therapy was designed, prepared and characterized. The physicochemical and biological data were presented and discussed. Their two‐photon absorption cross section was determined, revealing quite good performances of the compounds (δ ≈ 300 GM at 880 nm for2 and3 and δ ≈ 1000 GM at 840 nm for5 and6 ). Despite their promising photophysical properties, porphyrin dimers are penalized by their low solubility and an insufficient penetration into tumour cells. Incorporation into nanocarriers such as lipid vesicles could be profitable, provided that the positioning and degree of freedom of the saccharide moieties are optimal to target the receptors of the cells of interest. Abstract : Glycoconjugated porphyrin dimers usable in 2PA PDT were designed and characterized. Their 2PA cross section was determined, (2 ‐3, δ ≈ 300 GM at 880 nm and 5‐6, δ ≈ 1000 GM at 840 nm). Despite their promising photophysical properties, dimers are penalized by a low solubility and a weak penetration into cells. Incorporation into nanocarriers could be profitable, provided that the positioning and degree of freedom of the saccharide parts are optimal to target the receptors of the tumor cells.